SERVICE QUALITY IMPROVEMENT STRATEGY USING AN IMPORTANCE-PERFORMANCE ANALYSIS APPROACH - Simanjuntak, Megawati; Pratiwi, Ismayanti (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Changes in people's lifestyles increase the demand for health services. From a business point of view, competition is now getting tougher, so every hospital must work hard to survive in the health service industry through efforts to increase customer satisfaction with available services. This study used the Importance Performance Analysis and Customer Satisfaction Index methods to measure customer satisfaction at XYZ Mental Hospital Bogor with a sample of 400 respondents. Data collection was carried out through interviews with the help of questionnaires and open questions about complaints. Service quality is measured by the SERVQUAL method, which consists of five dimensions: physical evidence, reliability, responsiveness, assurance, and empathy. The results show that four service attributes must be improved because they have low performance but are considered important to customers. In addition, there are four other attributes in quadrant three and the four attributes with the lowest CSI scores, so it is also important to make improvements. The result shows that the CSI value of XYZ Mental Hospital is 81.86, which means that the service is in a good category. However, this value has not reached the value targeted by the hospital.